The Value of Local Wisdom in The Traditional Game Ngejuk Capung - Purnami, Ida Ayu Putu (Jurnal Pendidikan dan Pengajaran, 2025)
The traditional game of ngejuk capung is one of the cultural heritages that is beginning to be abandoned. This is influenced by the rapid development of technology, to the extent that children today only play online games and forget about traditional games. However, traditional games contain noble cultural values that have been passed down from generation to generation. The purpose of this study is to identify the local wisdom values in the ngejuk capung game. The research method used is a descriptive qualitative method. The data collection technique involved a literature review of the traditional game series by Made Taro, from “Ngejuk Capung” to “Ngejuk Lindung,”. The instruments used were an analysis sheet (data coding tool) and field notes.  The results of this study indicate that the seemingly simple ngejuk capung game actually contains 17 local wisdom values, namely religious values, aesthetic values, cooperative values, moral values, tolerance values, artistic values, historical values, economic values, social values, hard work values, discipline values, educational values, health values, cultural preservation and creativity values, environmental care values, peace values, and courtesy values. The local wisdom values contained in the ngejuk capung game can serve as a model for developing multicultural education that values diversity while maintaining cultural identity. The long-term implications of this research are the opening of opportunities to develop an educational curriculum that not only focuses on academic achievement but also on the formation of strong character, social awareness, and love for local culture.